Birds and places: What the lexicon reveals about multilingualism. (August 2021) - Döhler, Christian
Aims and objectives: The paper describes the current multilingual language ecology and explores two subdomains of the lexicon in order to infer information about the extent and nature of multilingualism in the past. Methodology: The paper employs quantitative and qualitative analysis of a sociolinguistic questionnaire in the first part. The second part includes a qualitative analysis of lexemes in the domains of bird names and plant names, and then compares them with old ethnographic sources as well as recent information on the surrounding languages. Data: The data of this study come from original fieldwork by the author in the village of Rouku and surrounding villages collected between 2010 and 2016. It is supplemented by material from colleagues working on related languages (Evans, Kashima and Siegel). Findings: The method suggests that the type of multilingualism that was practiced in the past is similar to today. Originality: The study is novel in providing a description of multilingualism from the Southern New Guinea area. Moreover, it advances a lexicographic and ethnographic approach in reconstructing the past state of a language ecology. Implications: The main conclusion is that in the absence of written historical sources – a problem that one is almost always facing in New Guinea – it is possible to extrapolate from the lexicon of Komnzo to a past state of the local language ecology. Limitations: The method does not allow for dating the point in time for which the inferences can be made.